1981
DOI: 10.1177/002383098102400202
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Language Phonetic Interference: Arabic to English

Abstract: This study compares phonetic implementation of the stop voicing contrast produced in Arabic by Saudi Arabians and by both Americans and Saudis in English. The English stops produced by Saudis manifested temporal acoustic correlates of stop voicing (VOT, stop closure duration, and vowel duration) similar to those found in Arabic stops. Despite such phonetic interference from Arabic to English, however, American listeners generally had little difficulty identifying the English stops produced by the Saudis, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

28
195
4
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 214 publications
(234 citation statements)
references
References 23 publications
28
195
4
1
Order By: Relevance
“…The phonemic vowel length hypothesis predicts that Arabic speakers should use vocalic duration extensively in production and perception. On the contrary, Experiment 1 revealed that, consistent with Flege and Port's (1981) findings, they produced only slightly (but significantly) longer vocalic segments in their pod tokens. It further indicated that their productions showed a significant variation in F1 offset as a function of final stop voicing.…”
supporting
confidence: 73%
“…The phonemic vowel length hypothesis predicts that Arabic speakers should use vocalic duration extensively in production and perception. On the contrary, Experiment 1 revealed that, consistent with Flege and Port's (1981) findings, they produced only slightly (but significantly) longer vocalic segments in their pod tokens. It further indicated that their productions showed a significant variation in F1 offset as a function of final stop voicing.…”
supporting
confidence: 73%
“…Some studies, particularly for highly proficient early bilinguals, have shown that bilinguals are capable of producing segmental features in line with those of the corresponding monolingual populations (Nathan, Anderson & Budsayamongkon 1987, Mack 1989, Magloire & Green 1999, Macleod & Stoel-Gammon 2005. Other studies, however, have shown that, while maintaining different norms for their two languages, bilingual phonetic productions are not necessarily identical to monolingual norms (Flege & Port 1981, Flege & Hillenbrand 1984, Major 1987, with bilinguals generally showing some degree of convergence towards the opposite language norms (Caramazza et al 1972;see Flege & Eefting 1987, for both convergence and divergence). Although there is some debate regarding the underlying processes responsible for acquisition, the existence of dual phonetic systems holds for both early simultaneous bilingual acquisition (Unitary System Model, e.g.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Languages like Arabic (Flege & Port, 1981), Saraiki , Dutch (Simon, 2009(Simon, , 2011, Spanish (Flege & Eefting, 1988), Russian (Backley, 2011), Japanese (Shimizu, 2011), Hungarian (Lisker & Abramson, 1964, etc. are considered voicing languages but German (Hamann, 2011), English (Honeybone, 2005), Swedish, Korean, Icelandic (Backley, 2011), etc.…”
Section: The Voiced Plosives /B D G/mentioning
confidence: 99%